PERSPEKTIF GURU TENTANG PENGEMBANGAN SMA DI TANGERANG PADA MASA PANDEMI COVID-19. - muh Turizal Husein; Sah lani (Rausyan Fikr : Jurnal Pemikiran dan Pencerahan, 2021)
ABSTRACTThis article focuses on the challenges of teachers at high schools related to the digitalization process in school development during the Covid-19 pandemic. In addition to being an intrapersonal prerequisite for teaching with technology and changing attitudes towards learning and teaching, it is a prerequisite for schools as part of a learning organization. This research is a qualitative research with a qualitative interview study of 10 participants or teachers. This was done to identify challenges for teachers, the role of ship principals, and collaboration among stakeholders. The strategy of teaching methods using technology proved to be a clear agenda by school principals regarding reliable technology infrastructure and also the willingness of teachers to use teaching methods.